Collaborative Learning in Sociology Research Methods Courses: Does Race Matter?. (October 2020) - Morris, Patricia; Ida, Aya Kimura; Migliaccio, Todd; Tsukada, Yusuke; Baker, Dylan
Students often identify research methods classes as one of the most difficult and intimidating classes of their academic career. The objectives of this study were twofold. The first was to ascertain whether the use of group-centered, collaborative learning would improve student mastery of material compared to traditional, lecture-based classes. The second objective was to examine a possible differential impact of collaborative learning by race. The study measured students' mastery of basic concepts in research methods as well as their application of the material to novel situations by comparing their competence at the beginning to their performance on the same measures at the midterm and final exams. Findings highlight the importance of examining race as a factor in the study of the effectiveness of collaborative learning and, more specifically, point to a need to further test the hypothesis that collaborative learning pedagogy techniques can ameliorate race-based achievement gaps in student performance.